EVALUATING R&D PREMIUM IN THE INDIAN HEALTH AND PHARMACEUTICALS INDUSTRIES - Bhumiswor Sharma; Srikanth Pyati (Jurnal Manajemen dan Kewirausahaan, 2022)
The economic advantages of research and development (R&D) investment have shown conflicting results in empirical studies. This study aimed to examine a different approach, evaluating R&D premium and cross-sectional variability of equity returns, a particular case for the Indian healthcare industry. The primary motivation for this study arrived from the size of the healthcare industry, the world's third-largest and India's largest industry, and the investment made in R&D activities. Results demonstrated that India's annualized R&D premium was significantly greater than the current value, investment, profitability, and momentum premiums. It indicated that the new R&D risk factor in pricing models is a primary reference for Indian equity investors, particularly for companies with R&D spending. Results were robust in evaluating portfolio return using univariate and multivariate tests. Findings suggested that R&D augmented models outperformed conventional pricing models, denoting that the R&D factor undoubtedly revealed priced element and vital risk factor in designing pricing models for emerging countries like India. When adjusting to R&D investment and trading strategies, policymakers, and financial professionals should hereby evaluate their risk-return implications